Limited evidence and ethical considerations in rTMS trials for adolescents with obsessive–compulsive disorder - Raphael J. Leo; Brandon L. Mariotti (BJPsych Bulletin)
Repetitive transcranial magnetic stimulation (rTMS) has gained regulatory approval as an adjunctive treatment for obsessive–compulsive disorder (OCD) in adults. However, its application in adolescents remains largely untested. This editorial examines the limited evidence available, focusing on choice of target, stimulation depth and methodological variation. Ethical challenges surrounding the use of rTMS in vulnerable populations, including informed consent and the unknown long-term effects on neurodevelopment, are also discussed. Although rTMS holds promise for treatment-resistant adolescent OCD, a cautious and ethically rigorous approach is essential before wider clinical adoption can be considered.